Indirect methods to estimate canopy coverage of clonal eucalypt plantations - Monte, Marco Antonio; Reis, Maria das Graças Ferreira; Reis, Geraldo Gonçalves dos; Leite, Hélio Garcia; Stocks, Jonathan James (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate methods to process digital photographs in order to estimate the canopy coverage index (CCI), to replace the use of leaf area index (LAI). Digital photographs with 640x480 and 1,280x960 pixels were processed with the Erdas Imagine, Gap Light Analyzer and Sidelook softwares. Leaf area index, using the LAI-2000, and digital photographs were obtained from pruned and thinned Eucalyptus grandis clone plantations at 81 and 93 months of age. Significant correlations were observed between LAI and CCI. Greater sized photographs (1,280x980 pixels) allowed better differentiation between sky and canopy pixels. Canopy Coverage Index obtained from digital photographs processed with the Sidelook was better correlated with LAI than that obtained by Erdas Imagine and Gap Light Analyzer. It is possible to use digital photography for eucalypt forest CCI estimation.